Moral suffering among nurse educators of technical courses in nursing - Duarte,Carla Godinho (2017)
ABSTRACT Objective: to understand situations of moral suffering experienced at work by nurse educators of technical courses in nursing. Method: a qualitative study with discursive textual analysis by means of semi-structured interviews with ten nurse educators at two professional educational institutions in southern Brazil. Results: two categories were established: lack of commitment on the part of students to the future profession, expressed through disrespect and disregard for the work of nurse educators, with inappropriate behaviors and attitudes; and lack of commitment to the learning-teaching process, expressed by indifference to the professional profile and lack of interest in lessons and care practices associated with learning gaps. Conclusion: these situations have an impact on experiences of moral suffering by nurse educators, and show a need for rethinking their practice, relationships, and educational spaces, and implementing strategies to favor the confrontation of dilemmas and conflicts experienced in educational practice in technical courses in nursing.